ANÁLISE DE MODELOS DE FLUXOS DE AR PARA CONFORTO AMBIENTAL ASSISTIDA POR SIMULAÇÃO COMPUTACIONAL EM VOXELS - ARTHUR EMMANUEL DE MEDEIROS NÓBREGA (2022)
NÓBREGA, A. E. de M. Analysis of airflow models for environmental comfort assisted by computer simulation in voxels. 2022. Thesis (PhD) - Federal University of Mato Grosso do Sul. The ventilation models are suitable for designing spaces with environmental comfort. Based on these standards and according to studies that relate the built design to climatic aspects, the characteristics of the buildings can be oriented towards the use of air flows bringing greater environmental adequacy to the conditions of human occupation in the built object. The main objective of the work lies in the computational simulation of air flows over the built spaces. These flows are represented in voxel technology, which consist of minimal spatial units capable of graphically describing sparse volume objects. Visualization of volumetric data are used to analyze the use of ventilation in buildings. The consultation with the tradition of environmental comfort models at Princeton University supports the development of this work in the provision of ventilation arrangements for studies tested by simulation in voxels. Keywords: volumetric data, built design, ventilation, sparse volumes.